2017
DOI: 10.1248/bpb.b16-00991
|View full text |Cite
|
Sign up to set email alerts
|

Protection of the Blood–Brain Barrier as a Therapeutic Strategy for Brain Damage

Abstract: Severe brain damage by trauma, ischemia, and hemorrhage lead to fatal conditions including sudden death, subsequent complications of the extremities and cognitive dysfunctions. Despite the urgent need for treatments for these complications, currently available therapeutic drugs are limited. Blood-brain barrier (BBB) disruption is a common pathogenic feature in many types of brain damage. The characteristic pathophysiological conditions caused by BBB disruption are brain edema resulting from an excessive increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 70 publications
0
13
0
3
Order By: Relevance
“…AQP4, a critical component of an integrated water and potassium homeostasis ( Yukutake and Yasui, 2010 ), the expression has not changed after EA. Also, we found that EA stimulation at these parameters did not cause brain edema, which usually occurs after destruction of the BBB ( Michinaga and Koyama, 2017 ). Neuroglia, especially microglia and astrocytes, provide dynamicity to the brain.…”
Section: Discussionmentioning
confidence: 95%
“…AQP4, a critical component of an integrated water and potassium homeostasis ( Yukutake and Yasui, 2010 ), the expression has not changed after EA. Also, we found that EA stimulation at these parameters did not cause brain edema, which usually occurs after destruction of the BBB ( Michinaga and Koyama, 2017 ). Neuroglia, especially microglia and astrocytes, provide dynamicity to the brain.…”
Section: Discussionmentioning
confidence: 95%
“…Of note, brain endothelial cells are the main component of the NVU. Compromise of the NVU during ischemia results in BBB disruption and the influx of inflammatory cells and substances from the systemic circulation which amplifies brain injury [34]. The elucidation the molecular mechanisms underlying ischemic BBB damage is pivotal to understand NVU impairment during ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Kerapatan pada sel-sel endotel sawar darah otak didukung oleh adanya Tight Junction (TJ) yang terdiri atas beberapa protein, yaitu claudin-5 (CLN-5), occludin, dan Zonula occludens-1 (ZO-1). [17] Tight Junction merupakan pertahanan pertama yang dimiliki oleh sawar darah otak. Nantinya TJ akan menghambat gerakan seluruh molekul, kecuali molekul yang mampu melewati membran sel dengan kelarutannya dalam lemak (contohnya oksigen, karbon dioksida, etanol, dan hormon-hormon steroid) dan yang dapat melewati sistem transpor spesifik (contohnya glukosa dan asam amino).…”
Section: Hasil Penelitianunclassified